1975
DOI: 10.1121/1.380654
|View full text |Cite
|
Sign up to set email alerts
|

Physiological correlates of intonation patterns

Abstract: An experiment has been performed to assess to what degree laryngeal muscle activity and subglottal air pressure affect the rate of vocal cord vibration in speech. Attention has been limited to those changes in the rate of vocal cord vibration that are associated with the physiological implementation of prosodic phenomena such as intonation and prominence. Subglottal air pressure was measured directly through a catheter inserted between the cricoid and thyroid cartilages. Using hooked-wire electrodes, the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 0 publications
5
51
0
Order By: Relevance
“…24 A frequency variation of about 7 semitones (%50%) is used for intonation during normal phonation. 3,13 Besides the low pitch of the TE voice, for some laryngectomized patients another problem in voice rehabilitation is the low tonicity of the pharyngoesophageal segment, which results in a breathy TE voice of poor quality. 2,17 To improve voice quality in female laryngectomized patients and in patients with a hypotonic or atonic pharyngo-esophageal segment, recently several soundgenerating prosthetic prototypes have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…24 A frequency variation of about 7 semitones (%50%) is used for intonation during normal phonation. 3,13 Besides the low pitch of the TE voice, for some laryngectomized patients another problem in voice rehabilitation is the low tonicity of the pharyngoesophageal segment, which results in a breathy TE voice of poor quality. 2,17 To improve voice quality in female laryngectomized patients and in patients with a hypotonic or atonic pharyngo-esophageal segment, recently several soundgenerating prosthetic prototypes have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that declination was expected and used for normalization by listeners, i.e., when two stressed syllables sounded equal in pitch, the second was actually lower [3]. The physiological causes for F 0 declination include the tracheal pull [4], the downtrend of subglottal pressure [5,6], and the activity of laryngeal muscles [7]. It has been unclear, however, whether declination is part of the linguistic code and speaker-controlled, or an automatic byproduct of some physiological process [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, we would like to note that our interpretation of the SH reduction phenomena is partly in contradiction with the two extreme views about the SH muscle: the view that sees straightforward causal relationship between SH activity and F0 lowering (Sugito, 1982) and the view that sees virtually no role played by the SH regarding F0 lowering (Collier, 1975;Fujisaki, 1988).…”
Section: Suppression Of Sh and The Laryngeal Statementioning
confidence: 41%
“…The effect of NP location on F0 estimation implies that the efficiency of the CT activity is higher in earlier portion of an utterance than in later portion, and suggests the possible relevance of the subglottal pressure change. As mentioned briefly in Collier (1975), the CT activity can increase in order to compensate lowered subglottal pressure, which is observed typically in the realization of the sentence final rising rendition. If this kind of compensation exists throughout the sentence as a function of gradually decreasing subglottal pressure, the underestimation in the first noun phrase and the overestimation in the second one can be interpreted as a natural byproduct of the fact that we used one single regression formula to derive the estimated F0' value regardless of the phrase location.…”
Section: Systematic Deviations In the F0 Estimationmentioning
confidence: 99%
See 1 more Smart Citation